Faktor-Faktor Yang Mengakibatkan Tingginya Lead Time Pengiriman Obat Dari PBF Di Rumah Sakit Cahya Kawaluyan - Roma Ave Maria; Annizar Yanandra Eka Putri (CV. Multi Kreasi Media, 2022)
Drug procurement is an important role in preventing drug shortages. The problem that often results in drug shortages is the long lead time for drug delivery. This study aims to determine the factors that cause the long delivery of drugs from pharmacy wholesalers to the pharmaceutical installation of Cahya Kawaluyan Hospital. The research was conducted using sequential explanatory designs and quantitative-qualitative data collection. Quantitative data was obtained by collecting drug lead time data from ordering to receiving drugs at Cahya Kawaluyan Hospital for the January-March 2022 period and qualitative data obtained from interviews with Pharmacists and Pharmacy Technical Personnel for drug procurement. The results showed that there was a discrepancy in the waiting time for drug delivery from partner PBF to the maximum limit specified in the SOP. There were 20 PBF of 25 PBF that did not comply with the maximum limit. Factors that are the reasons for the delay in the arrival of drugs are: demand for drug purchases is quite high at pharmacy wholesalers, limited stock of pharmaceutical preparations at PBF, drug expiration date is approaching, drug orders from the Social Security Administering Agency (BPJS) through e-purchasing and imported drugs, as well as invoice revisions. because checking between goods and invoices is not appropriate and does not reach the minimum order.